Applying the Family Functioning Model to Explore Positive Support in Diabetes Self-Management: A Qualitative Study - Rian Adi Pamungkas; Kanittha Chamroonsawasdi; Haeril Amir; Andi Mayasari Usman; Abdurrasyid Abdurrasyid (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Family members play a vital role in helping and undermining diabetes mellitus self-management practice. Methods: A qualitative study design to describe and explore the potentially key family function in diabetes self-management (DMSM) practice. In-depth interview strategy and focus group discussion (FGD) were conducted at Community health centre. An open-ended approach was applied to elicit an answer from participants. A total of twenty-two participants were involved in this study. All interview and FGD processes were audiotaped and transcribed verbatim. Results: The results found that positive function of family to support DMSM practice such as 1) positive encouragement and emotional support; 2) acknowledge responsibility for shared management; and 3) console, encourage and remind to maintain behaviours, regular blood glucose and medication adherence. the positive function of affective involvement such as 4) Be partners and work together in goal setting, action plan, and problem solving; and 5) accompanying for medical appointment and medical check-ups. Positive function in communication and problem solving such as 6) talking nicely and taking time to listen every compliance; and 7) partners recognize the needs of helping in crisis situation. Conclusion: Our findings provide insights regarding how family function may influence the adoption and maintenance of healthy behaviours. As the health providers look for approaches to improve the DMSM practice, this valuable finding was essential to understand how the family function can improve and empower patients in DMSM practice. The findings of this study recommend that community health center should involve the family members to maintain the self-management implementation. The component of family function based should be consider for program development among diabetes patients.